Relationship between vitamin D deficiency and atopy in children - Al Mahdi, Kulthum; Albrahim, Mariyah; Alkhars, Fatimah; Alkhalifah, Ola; Alaithan, Rabab; Alhajri, Fatimah (International Journal of Contemporary Pediatrics, 2018)
Along with its role in regulation of calcium metabolism and bone health, vitamin D is essential for immune system integrity. Vitamin D is an essential immunomodulatory vitamin that interact with the immune system in response to foreign antigens. This interaction is mediated by the vitamin D receptors (VDR) expressed on the surface of various immune cells. Vitamin D has an inhibitory effect on synthesis and release of immunoglobulin E and thus is closely related to atopic disorders. Vitamin D deficiency is a risk factor for bronchial asthma, and it increased asthma-related exacerbation. Low vitamin D levels are encountered in patients with allergic rhinitis and increase the severity of the disease. Other allergic conditions such as atopic dermatitis, contact dermatitis, and food allergy were reported to be significantly correlated with vitamin D serum levels. Despite the established correlation between vitamin D and atopic disorders, double-blinded randomized controlled studies are still lacking to approve this relationship and to provide clear guidelines for the recommended supplementary doses of vitamin D to prevent or treat these conditions. This article aims to review the relationship between vitamin D deficiency and atopy in children.